SINGLE AND MULTIPLE ISCHEMIC BRAIN MICROLESIONS AFTER CAROTID ARTERY STENTING - E. S. Bulgakova; T. V. Tvorogova; В. A. Rudenko; O. М. Drapkina (Столичная издательская компания, 2018)
Aim. To identify most probable cardiovascular predictors of periprocedural ischemic brain microlesions after carotid artery stenting (CAS) accounting its presumable pathogenesis.Material and methods. 84 patients with carotid artery stenosis undergoing CAS in a specialized medical center were examined. Diffusion-weighted imaging (DWI) magnetic resonance imaging was performed in all patients before and after intervention.Results. Among selected patients aged 40 to 83 years (mean age of 60.6Ѓ}3.9 years, male 80.95%) 39 (46.4%) patients had new ischemic brain microlesions after CAS, differently located. Among all patients (n=84) microlesion count correlated with age (γ=0.243; p<0.01), preprocedural hemoglobin level (γ=-0.278; p<0.01), systolic blood pressure (SBP) level before CAS (γ=0.190; p<0.05) and diastolic blood pressure (DBP) level 1 hour after CAS (γ=-0.201; p<0.05). In patients with microlesions their count (n=39) correlated with SBP and DBP levels 15 min after CAS (γ=-0.370; p<0.01 and γ=-0.369; p<0.01, respectively), percentage of SBP and DBP levels decrease during CAS (γ=0.404; p<0.01 and γ=0.458; p<0.001, respectively), SBP level 24 h after CAS (γ=-0.272; p<0.05) and body mass index (γ=-0.260; p<0.05). Patients with multiple microlesions (n=25) differed from patients without lesions (n=45) older age (67.0 [64.0; 77.0] vs 64.0 [60.0; 70.0], p<0.05), lower preprocedural hemoglobin level (130.9Ѓ}14.5 vs 139.5Ѓ}13.6, p<0.01), lower percentage of smokers (32.0% vs 57.8%, p<0.05), previous ipsilateral stroke (36.0% vs 13.3%, p<0.05) and persistent periprocedural arterial hypotension (12.0% vs 2.2%, p<0.05). These patients with multiple microlesions had more significant DBP level decrease (17.0 [10.0; 25.0] vs 6.5 [1.3; 11.8], p<0.05) compared with patients with single lesions (n=14). In the group of patients with single brain microlesion, unstable (71.4% vs 40.0%, p<0.05) and calcified (64.3% vs 28.0%, p<0.05) atherosclerotic plaques were seen more often compared with patients with multiple lesions. Patients with single brain microlesion differed from patients without lesions greater frequency of calcified atherosclerotic plaques (64.3% vs 31.1%, p<0.05), usage of proximal embolic protection devices (21.4% vs 0.0% p<0.01) and predilatation (35.7% vs 13.3%, p<0.05), perioperative neurological symptoms (21.4% vs 4.4%, p<0.05, and higher SBP levels during 24 h after CAS (mean values 137-122 mm Hg vs 120-112 mm Hg, p<0.05).Conclusion. Single microlesion is associated with unstable or calcified plaques and CAS technical complexities. Multiple microlesions may be associated with periprocedural hemodynamic instability and cerebral hypoperfusion risk factors.